Orange Smith papers - Smith, Orange
Letters written by Smith to his brother while serving with Company C, 13th Connecticut Infantry Regiment at New Orleans, Baton Rouge, and Thibodaux, La., near Charleston, S.C., and Harrisonburg, Va. Includes a brief typewritten summary of each letter and photocopies of Company C muster rolls.
In part, photocopies.
Union army soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army. -- Connecticut Infantry Regiment, 13th (1862-1866); Baton Rouge (La.) -- History; Charleston (S.C.) -- History -- Civil War, 1861-1865.; Harrisonburg (Va.) -- History; Louisiana -- History -- Civil War, 1861-1865.; New Orleans (La.) -- History -- Civil War, 1861-1865.; South Carolina -- History -- Civil War, 1861-1865.; Thibodaux (La.) -- History; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; Soldiers